A distribution-free newsboy problem with fuzzy-random demand. Issue 3 (3rd July 2018) - Adhikary, Krishnendu; Roy, Jagannath; Kar, Samarjit
Abstract: This paper introduces a distribution-free newsboy problem in a fuzzy-random environment. The aim of the paper is to extend the distribution-free newsboy problem to the case where the demand is a fuzzy-random variable. We analyse the distribution-free model in which the mean and variance of the demand are known and the associated probability distribution is unknown. The problem is formulated for finding the simple closed-form solution of the optimal order quantity for the distribution-free newsboy model with fuzzy-random demand and then compared with a similar model where the product demand was considered as a random variable. Finally, some numerical examples are provided to illustrate the utility of the results. The applied sensitivity analysis, by changing the mark-up value, discount rate and demand deviation, demonstrates how a decision-maker can set (increase) his/her target profit using a distribution-free newsboy model under fuzzy-random demand.